Pengaruh Massa Adssorben Terhadap Adsorpsi Pergasol Red Dengan Proses Batch Menggunakan Cangkang Kulit Telur Terkalsinasi - Sanredina Sanredina; Rozanna Sri Irianty; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Waste dye untreated directly discharged into the environment and society can result in negative impacts on people's lives. One effort to reduce the content of azo dyes in solution Pergasol Red namely the adsorption process. The purpose of this study to determine the effect of mass adsorption at adsorption Pergasol Red uses powdered eggshells calcined. Pergasol Red 60 ppm solution of 200 mL added with a trowel powdered eggs with a variety of mass 1 g and 2 grdidalam erlenmeyer stirred with a speed of 200 rpm 40 ° C. Then the solution was analyzed using a UV-VIS spectrophotometer to determine the final concentration Pergasol Red after absorption. The more the number of egg shell powder mass concentration Pergasol Red adsorbed higher. A mass of 1 g and 2 g Pergasol Red adsorbed concentration as much as 56.3 ppm and 57.6 ppm with the effectiveness of the absorption of 96.1%. Keywords: adsorption, skin powdered eggs, Pergasol Red,